Menguji Validitas Dan Reliabilitas Pada Mata Pelajaran Al Qur’an Hadits Menggunakan Korelasi Produk Momenspearman Brown - Vick Ainun Haq (Indonesia, 2022)
Having a passion for learning is an important role in education, apart from being an encouragement for students to achieve optimal understanding, learning motivation also plays a role as a determinant of learning outcomes and student achievement. Therefore, a measuring tool is needed in the form of a learning motivation questionnaire, this will be done in testing the validity and reliability of the Al-Quran Hadith subjects. This study aims to describe the methods and steps of testing the validity of the questionnaire instrument, the reliability correlation test coefficient and the reliability test. The method used is a qualitative approach, by collecting data, calculating and analyzing data. The results of this study (1) find out how to measure reliability with internal consistency, the split half method, using the moment product formula Spearman Brown (2) find the level of validity of the questionnaire instrument which is declared good, namely 0.682, showing the coefficient of reliability correlation exceeds the product moment value of 0.725 and the reliability test was stated to be reliable with a high level of 0.841 (3) that the evaluation instrument, scoring administration instrument and answers from students were factors that influenced validity.